Development of a SiYAlON glaze for improved osteoconductivity of implantable medical devices. Issue 3 (15th May 2017) - Bock, Ryan M.; Marin, Elia; Rondinella, Alfredo; Boschetto, Francesco; Adachi, Tetsuya; McEntire, Bryan J.; Bal, B. Sonny; Pezzotti, Giuseppe
Abstract: The application of bioactive coatings onto orthopaedic appliances is commonly performed to compensate for the otherwise bioinert nature of medical devices and to improve their osseointegration. Calcium phosphates, hydroxyapatite (HAp), and bioglasses are commercially available for this purpose. Until recently, few other inorganic compounds have been identified with similar biofunctionality. However, silicon nitride (Si3 N4 ) has emerged as a new orthopaedic material whose unique surface chemistry also enhances osteoconductivity. Recent research has confirmed that its minority intergranular phase, consisting of silicon yttrium aluminum oxynitride (SiYAlON), is principally responsible for this improvement. As a result, it was hypothesized that SiYAlON itself might serve as an effective osteoconductive coating or glaze for medical devices. To test this hypothesis, a process inspired by traditional ceramic whiteware glazing was developed. A slurry containing ingredients similar to the intergranular SiYAlON composition was applied to a Si3 N4 surface, which was then subjected to a heat treatment to form a glaze. Various analytical tools were employed to assess its chemistry and morphology. It was found that the glaze was comprised predominately of Y5 Si3 O12 N, a compound commonly referred to as N‐apatite, which is isostructural to native HAp. Subsequent exposure of the glazed surface to acellular simulated body fluid led to increased deposition of biomimetic HAp‐like crystals, while exposure to Saos‐2 osteosarcoma cells in vitro resulted in greater HAp deposition relative to control samples. The observation that SiYAlON exhibits enhanced osteoconductivity portends its potential as a therapeutic aid in bone and tissue repair. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1084–1096, 2018.